Interpersonal Skills in English Speaking Classrooms: A Sociopragmatic Study in an Indonesian Pesantren - Moh Kholid; Indi Azimah; Salsabila Umi Nur Fajria; Khoirotun Nissak; Dzulfikri Dzulfikri (Abjadia : International Journal of Education, 2026)
This qualitative study explores how interpersonal communication strategies, framed within the concept of “loving pedagogy,” shape the relational dynamics of English-speaking classrooms in an Indonesian Islamic boarding school (pesantren). Conducted at Pesantren Luhur Baitul Hikmah in Kepanjen, Malang, the research involved two English teachers and three students (santri). Data were collected through semi-structured interviews and analyzed thematically. Findings reveal that teachers employ culturally situated strategies- such as non-threatening error correction inclusive language, and the framing of English as a tool for collective religious and intellectual purposes- to build psychologically safe learning environments. For instance, teachers consistently used praise –first recasts (e.g., “Good attempt, let’s just adjust the verb form together”) and positioned speaking practice as ibadah dakwah, which visibly lowered students’ affective filters. These practices reduce students' speaking anxiety and enhance their willingness to communicate. The study demonstrates that effective interpersonal pedagogy in this context is deeply interwoven with local ethical and mentorship traditions (Suhbah). The results offer a model for culturally responsive language teaching that integrates relational care with pedagogical intentionality, providing practical insights for teacher development in Islamic educational settings.